Branched Gold Nanoparticle Coating of Clostridium novyi‐NT Spores for CT‐Guided Intratumoral Injection. Issue 5 (15th November 2016) - Park, Wooram; Cho, Soojeong; Huang, Xiaoke; Larson, Andrew C.; Kim, Dong‐Hyun
Abstract : Branched gold nanoparticle (BGNP)‐coated Clostridium novyi‐ NT ( C. novyi ‐NT) spores are developed for computed tomography (CT)‐guided bacteriolytic tumor therapy. The BGNP‐coated spores are successfully injected into a tumor site under CT image guidance. As a result, a strong antitumor effect is observed in a PC3 prostate tumor‐bearing mouse model.